Determination of the relationship between percentage of hypo-osmotic swelling test scores and antisperm antibody assay in infertile patients after IUI technique - KH.Kouti, Bassim; M.Fakur Al deen, Mohammed – Baqer (University of Thi-Qar Journal of Science, 2009)
This study was devised to compare the results of hypo-osmotic swelling (HOS) test and antisperm antibody assay (ASA) for normozoospermic men and infertile patients affectedby autoimmune infertility. Thirty semen samples were collected by masturbation andprepared by direct layering technique for IUI procedure. Hypo-osmotic swelling test was performed by mixing 0.1 ml of semen with 1.0 ml of a 150mOsm/ L NaCl as a hypo-osmotic solution and direct immunobead assay were used todetermine the presence of ASA bound on the sperm surface. However, spermconcentration, sperm motility, progressive sperm motility, normal sperm morphologywere evaluated according to standard World Health Organization (WHO) criteria andsubjected to HOS test and ASA assay. The sperm prepared and incubated for 30 minutein 5% COat 37ºC after in vitro sperm preparation.The results reported that the percentage of HOS test score in ASA positive (55.20 ± 7.1)sperm samples was significantly lower than that noticed in ASA negative (73.32 ± 4.8)sperm samples (P<000.1). As a result, eight clinical pregnancy rates were accounts fornormozoospermic men without ASA and normal HOS test after in vitro sperm activationand IUI procedure. Therefore, it was concluded that the use of HOS test as a simple anddependable test to identify successful pregnancy after intra-uterine insemination. Furtherstudies are suggested to assess the effect of ASA on sperm plasma functional integrityafter ICSI and IVF-ET.